PEMBUATAN GENERATOR SINKRON UNTUK PEMBANGKIT LISTRIK TENAGA MIKROHIDRO DARI MAGNET MOTOR BEKAS DI DESA KEMUMU BENGKULU UTARA - ., Hendra; Syaiful, Muhammad; Indriani, Anizar (Dharma Raflesia : Jurnal Ilmiah Pengembangan dan Penerapan IPTEKS, 2017)
Community empowerment in improving the knowledge to make a generator by using the recycle of magnet of the motorcycle is part of a community service-based research through training manufacture of generators. This generator can be used to change of mechanical energy into the electrical energy. Where as the mechanical energy is obtained from the turbine screw. This training method contains material about the introduction of the generator and proceed with the process of manufacture of generators by using recycle of motorcycle magnet coil manner. Generators are made tested with the 3 phase of motors as early movers to get the magnitude of the voltage output of the generator. After the output voltage is obtained then followed by using the turbinesscrew, windmills or other propulsion to drive the generators. Magnet motor that is made into a generator consists of several magnetic poles are 6, 8 and 12 poles. Mechanism of the generator is expected to help the community in generating electrical energy as a power source of the electrical power and that does not depend anymore on electricity company such as PLN for lighting, drying, cooling and others. Through this training, the potential flow of a river or irrigation water in the village of Kemumu can be utilized by the villagers to meet the need for electrical energy. Where electrical energy can be used to increasing the economy value and daily life of rural communities Kemumu. Of the training conducted, it was found that the generator capable of producing an electrical voltage of 106 volts with the rotation drive of screw turbines is 876 rpm and 12 pole magnet generator. The generator with an output voltage of 6 obtained by 78, 4 Volt with one load of 15-watt incandescent light bulb. And using four load of 15-watt incandescent light bulbs obtained 58,8 Volt output voltage by using a magnetic generator 8 poles. From these results can be concluded that the generators by using the recycle magnet of motorcycle by the community can generate an electric voltage. Keywords: Generator, PLTMH, Electrical Energy, Magnet Motor, Turbin Screw